Cycloaddition Reactions of Carbonyl Ylides Derived From Enones - Yu, Yang; Cornelissen, Loïc; Wong, Wing-Tak; Chiu, Pauline (Synlett, 2015)
The formation of unsaturated carbonyl ylides via rhodium-catalyzed carbene cyclization with enones and their subsequent inter- and intramolecular cycloadditions to construct functionalized oxapolycyclic rings have been realized.
Keywords: carbenoids; ylides; cycloaddition; diazo compounds; domino reaction